Islam, terrorismo y derechos humanos - Portilla Gómez, Juan Manuel (Revista Mexicana de Política Exterior, 2022)
The terrorist attacks of September 11, 2001 spawned a spiral of violence, with terrorists and anti-terrorists turning the world into a merciless battlefield. In this essay, Juan Manuel Portilla Gómez looks at how the inappropriately dubbed “war” on Islamic terrorism has affected humanitarian law and human rights. A veritable crusade has been launched against thousands of foreign nationals, both in and beyond zones of conflict, giving rise to unsavory rumors about prisons like Guantánamo, Bagram and Abu Gharib; reports of unjustified arrests, with most of the detainees accused of being involved in terrorist activities later being released; the handing over of suspects —in flagrant violation of their human rights— to governments in their countries of origin, where they will most likely be subjected to uncensored torture and other inhumane forms of treatment; and talk of “ghost and itinerant prisoners” and secret detention centers. Portilla Gómez believes that the Military Commissions set up by the United States deny alleged terrorists their right to a fair trial, lacking as they do autonomy and impartiality. Crimes of terrorism should not be brought to justice in this discriminatory manner, he says, but, by virtue of their very nature, should be sanctioned via the existing mechanisms of international humanitarian and criminal law, whether committed in times of war or peace.